Comparative physiological analysis in the tolerance to salinity and drought individual and combination in two cotton genotypes with contrasting salt tolerance. Issue 2 (10th September 2018) - Ibrahim, Wasim; Qiu, Cheng‐Wei; Zhang, Can; Cao, Fangbin; Shuijin, Zhu; Wu, Feibo
Abstract : Soil salinity and drought are the two most common and frequently co‐occurring abiotic stresses limiting cotton growth and productivity. However, physiological mechanisms of tolerance to such condition remain elusive. Greenhouse pot experiments were performed to study genotypic differences in response to single drought (4% soil moisture; D) and salinity (200 mM NaCl; S) stress and combined stresses (D + S) using two cotton genotypes Zhongmian 23 (salt‐tolerant) and Zhongmian 41 (salt‐sensitive). Our results showed that drought and salinity stresses, alone or in combination, caused significant reduction in plant growth, chlorophyll content and photosynthesis in the two cotton genotypes, with the largest impact visible under combined stress. Interestingly, Zhongmian 23 was more tolerant than Zhongmian 41 under the three stresses and displayed higher plant dry weight, photosynthesis and antioxidant enzymes activities such as superoxide dismutase (SOD), peroxidase (POD) catalase (CAT) and ascorbate peroxidase (APX) activities compared to control, while those parameters were significantly decreased in salt‐stresses Zhongmian 41 compared to control. Moreover, Na + /K + ‐ATPase activity was more enhanced in Zhongmian 23 than in Zhongmian 41 under salinity stress. However, under single drought stress and D + S stress no significant differences were observed between the two genotypes. No significant differences were detected in Ca 2+ /Mg 2+ ‐ATPase activity in Zhongmian 41, while in Zhongmian 23 it was increased under salinity stress. Furthermore, Zhongmian 23 accumulated more soluble sugar, glycine‐betaine and K +, but less Na + under the three stresses compared with Zhongmian 41. Obvious changes in leaf and root tips cell ultrastructure was observed in the two cotton genotypes. However, Zhongmian 23 was less affected than Zhongmian 41 especially under salinity stress. These results give a novel insight into the mechanisms of single and combined effects of drought and salinity stresses on cotton genotypes.